Zimbabwe’s Magaya Decision Revisited: Women’s Rights and Land Succession in the International Context - Knobelsdorf, Valerie (Columbia Journal of Gender and Law, 2006)
When Shonhiwa Magaya died without a legal will, a local court in Zimbabwe designated his eldest child, Venia Magaya, heir to his estate. On appeal, Ms. Magaya’s younger half-brother claimed heirship on the grounds that according to African customary law, “a lady … cannot be appointed [as heir] to (her) father’s estate when there is a man” in the family who is entitled to claim it. An appellate magistrate agreed and Ms. Magaya’s heirship was reversed. The newly appointed heir took his position as head of household, removed Ms. Magaya from her family home, and placed her in a shack in the neighbor’s backyard. Upon further appeal, the Supreme Court of Zimbabwe upheld the appellate decision, stating that, despite constitutional protections against discrimination, the fact that this case arose under customary law exempted its discriminatory aspects from court scrutiny. The court explained that the constitution permits this type of discrimination against women as within “the nature of African society.” Magaya v. Magaya, the now-infamous Zimbabwe customary law and intestate succession case, triggered significant domestic and international opposition. Critics alleged that the decision was invalid under both Zimbabwean constitutional law and international law, violating “fundamental issues of fairness, international norms and rights, and even customary law itself.” Questions surrounding the outcome of Magaya still linger throughout southern Africa. On one hand, critics argue, legal and social norms require that female children and widows be given equal rights to property inheritance upon the death of a family member, particularly as economic and health crises have imposed a disparate impact on the resources of women throughout the region. On the other hand, legal decisionmaking is a delicate balancing process. Courts across southern Africa have upheld the cultural rights embodied in national constitutions as well as in numerous international human rights instruments, as a basis for autonomy and development. With strong legal protections for cultural practices and the application of customary law in Zimbabwe, one of the most troubling critiques of this case is the idea that this decision may have been the only outcome the court could have reached; that, even if the court had incorporated human rights considerations, the law in Zimbabwe so clearly sanctions gender-based discrimination that the case could not have come out any other way. Although this view is rather extreme, it demonstrates the scope and importance of the fundamental rights and freedoms at issue, and the legal obstacles that these rights face under Zimbabwean law. With such critical protections at stake, Magaya has raised the important question of whether a fundamental tension exists between anti-discrimination rights, particularly on the basis of gender, and the right to cultural self-determination, including a right to the application of customary law.